Comprehensive analysis of mitophagy-related genes reveals prognostic signatures in breast cancer: based on immune landscapes and treatment target predict - Zhao, Hejia; Zhang, Wanying; Du, Yiheng; Kuang, Zheng; Tan, Yilan; Chen, Yanjun; Ma, Yujie; Zou, Fei (Frontiers in Immunology, 2026)
BackgroundBreast cancer (BC) is a common malignant tumor with high incidence and mortality rates. Mitophagy refers to a selective form of autophagy that is believed to be closely related to the occurrence and progression of BC. Identifying the mitophagy-related sites associated with BC can help us gain a deeper understanding of the underlying mechanisms of BC, laying the foundation for early diagnosis and effective treatment of BC.MethodRNA-seq expression data of BC were obtained from the GEO and TCGA databases. Differentially expressed genes were intersected with mitophagy-related genes from GeneCards to identify BC-associated mitophagy genes. Prognostic biomarkers were screened using Kaplan–Meier (K–M) survival and ROC analyses. Based on mitophagy-related gene expression and survival data, BC patients were classified into high- and low-risk subgroups for immune infiltration and GSEA analyses. Finally, IHC data from the HPA database and in vitro experiments, including siRNA-mediated knockdown, Western blot, CCK-8 proliferation assay, confocal microscopy and drug prediction were performed to validate the expression and biological functions of candidate biomarkers PBK and NEK2.ResultThrough dual validation of K-M survival analysis and ROC diagnosis-treatment efficacy analysis, we ultimately identified 9 mitophagy-related prognostic biomarkers for BC, and found their expression was significantly upregulated in BC tissues. In addition, the results showed that the degree of immune infiltration in the low-risk subgroup was considered higher than that in the high-risk subgroup. Inhibition of PBK and NEK2 will have an inhibitory effect on the proliferation of BC cell. Furthermore, clinicopathological analyses confirmed a genuinely higher risk in the high-risk subgroup, with PBK and NEK2 independently associated with risk stratification.ConclusionThis study elucidated the prognostic value, immune microenvironment characteristics, and molecular mechanisms of mitophagy in BC, and identified nine mitophagy-related biomarkers. Among them, PBK and NEK2 were experimentally confirmed to promote tumor cell proliferation, providing novel insights for early diagnosis and therapeutic strategies in breast cancer.